2010
DOI: 10.1264/jsme2.me09182
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas Quinolone Signal Affects Membrane Vesicle Production in not only Gram-Negative but also Gram-Positive Bacteria

Abstract: Many Gram-negative bacteria naturally produce membrane vesicles (MVs) to the extracellular milieu. The Pseudomonas quinolone signal (PQS), a quorum-sensing signal of Pseudomonas aeruginosa, is a positive regulator of MV production. In this study, we investigated its effects on MV production in other Gram-negative and -positive bacterial species. The addition of PQS to an Escherichia coli K12 culture resulted in increased MV production and enlarged MVs. An excessive amount of MgCl 2 repressed E. coli MV product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 44 publications
0
60
0
Order By: Relevance
“…Significant decrease in the abundance of one LPS species in the OM altered protein cargo incorporated into MVs (27). Furthermore, treatment of the E. coli cell surface with Mg 2ϩ resulted in decreased MV production, supporting the idea that charge interactions on the cell surface (via the LPS O-antigen polysaccharide) influence MV release (89), and that substances acting on the cell surface in different environments may induce release of MVs with specific contents. Additionally, stimuli from within the bacterial cell can also influence MV release.…”
Section: Mechanisms Of Vesicle Biogenesismentioning
confidence: 71%
“…Significant decrease in the abundance of one LPS species in the OM altered protein cargo incorporated into MVs (27). Furthermore, treatment of the E. coli cell surface with Mg 2ϩ resulted in decreased MV production, supporting the idea that charge interactions on the cell surface (via the LPS O-antigen polysaccharide) influence MV release (89), and that substances acting on the cell surface in different environments may induce release of MVs with specific contents. Additionally, stimuli from within the bacterial cell can also influence MV release.…”
Section: Mechanisms Of Vesicle Biogenesismentioning
confidence: 71%
“…Thus, although the enzyme responsible for PQS formation from HHQ in P. aeruginosa is not yet described in P. putida, it seems reasonable that PQS or a very similar quorum-sensing molecule is involved in the release of MV in P. putida (7,8). This hypothesis is supported by the fact that exogenous PQS enhances MV production in P. putida (43).…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have reported that competitive or cooperative communication could occur between groups of bacteria or between bacteria and hosts (13,21,24,38). In particular, 3-oxo-C12-AHL produced by P. aeruginosa, possesses several functions against not only bacteria but also mammalian cells.…”
mentioning
confidence: 99%